Technological opportunities, academic research, and innovation activities in the German automobile supply industry - Jürgen Peters; Wolfgang Becker (Universität Augsburg, Institut für Volkswirtschaftslehre, 1998)
In this paper the importance and the effects of technological opportunities, stemming from academic research, on the innovation activities of firms in the German automobile supply industry are investigated. We observe that the contribution of academic research to firms' innovation activities is less important than the relevance of industrial sources but yet, the most likely partners for formal R&D co-operations are universities. Using measures of suppliers' innovation input and output, we can outline differences in the effects of academic research on suppliers' innovation behavior. Although the proximity to academic research stimulates suppliers' activities in own R&D, the university knowledge substitutes suppliers' investment in R&D and other innovation activities. University co-operations seem to have a positive impact on the improvement of existing rather than on the development of new products or processes. But we can show that the influence of academic research on suppliers' inhouse innovation activities depend on their absorptive capacities.
urn:nbn:de:bvb:384-opus4-252505
Keywords: O31; I20; H40; 330; Innovation Activities; Technological Opportunities; Academic Research; Absorptive Capacities; Automobile Supply Industry